The Relationship Of Mother's Behavior About Neck Cancer In The Papsmear Examination At The Pancur Batu Health Center Year 2020 - Siti Meilan Simbolon; Ristika Julianty Singarimbun (Jurnal EduHealth, 2021)
Cervical cancer has the highest incidence rate in developing countries and developed countries rank second after breast cancer. WHO notes that in the world every year there are 5.25 million people with cancer. Most sufferers come at an advanced stage to check themselves. Based on data from the Pancur Batu Health Center, every year the number of cervical cancer sufferers in 2019-2020 has increased from 96 people to 126 people. For this reason, researchers feel the need to conduct research on "The Relationship between Mother's Behavior About Cervical Cancer in Pap Smear Examination." The research design used was analytic with a cross-sectional and correlational approach using a questionnaire as a data collector. The research was conducted in March – June 2020. The population is mothers in the working area of ​​the Pancur Batu Health Center as many as 193 people and 38 people as samples (simple random sampling). Based on the results of the study, the level of knowledge of mothers about cervical cancer was moderate, as many as 27 people (71.1%), attitudes towards pap smear examination were positive, as many as 31 people (81.6%) and the relationship showed a strong correlation, namely the value of 0.567. The level of education was quite influential on the level of knowledge of mothers about cervical cancer. It is hoped that health workers will increase the provision of information through counseling and ultimately reduce maternal morbidity and mortality. attitude towards pap smear examination was positive as many as 31 people (81.6%) and the relationship showed a strong correlation, namely the value of 0.567. The level of education was quite influential on the level of knowledge of mothers about cervical cancer. It is hoped that health workers will increase the provision of information through counseling and ultimately reduce maternal morbidity and mortality. attitude towards pap smear examination was positive as many as 31 people (81.6%) and the relationship showed a strong correlation, namely the value of 0.567. The level of education was quite influential on the level of knowledge of mothers about cervical cancer. It is hoped that health workers will increase the provision of information through counseling and ultimately reduce maternal morbidity and mortality.